SOFT COMPUTING IN MODERN philology - Краснюк, С.О.; Гончаренко, С.М.; Любимова, Н.В.; Денисенко, В.М.; Петренко, В.Ю. (Modern engineering and innovative technologies, 2024)
The relevance of soft computing in modern philology is growing along with the need to analyze and process large amounts of linguistic data containing complex, ambiguous and culturally determined aspects. Soft computing opens up new possibilities for the s